Dietary index for gut microbiota and its inverse association with female infertility: evidence from NHANES 2013–2018 - Cheng, Chiqiang; He, Xi; Zhou, Chunhua; Ouyang, Liu; Zhao, Yang; Li, Jiahui; Liu, Fangfang; Gao, Xia (Frontiers in Nutrition, 2025)
BackgroundInfertility has become a global health concern, especially as the aging population continues to grow. Previous studies suggest that gut microbiota plays a crucial role in female reproductive health. This study aimed to investigate the association between the Dietary Index for Gut Microbiota (DI-GM) and female infertility.MethodsWe analyzed data from 8,910 participants aged 20–45 years in the NHANES 2013–2018 cycles. DI-GM scores were calculated based on dietary recall interviews, including 14 foods and nutrients associated with gut health. Female infertility was identified through reproductive health questionnaires. Weighted logistic regression models were used to assess the relationship between DI-GM and infertility, with adjustments for demographic, lifestyle, and health-related covariates. Restricted cubic spline (RCS) analyses explored non-linear associations, and subgroup analyses ensured the robustness of the results.ResultsA significant negative association was observed between DI-GM and female infertility (adjusted OR = 0.89, 95% CI: 0.83–0.95, p < 0.001). Participants with DI-GM scores ≥6 had a 40% lower risk of infertility compared to those with scores 0–3 (OR = 0.60, 95% CI: 0.44–0.82, p = 0.001). RCS analyses revealed an L-shaped non-linear relationship, with a threshold at DI-GM = 5. Subgroup analyses indicated stronger associations in women with lower education levels and those with coronary heart disease (P for interaction <0.05).ConclusionOur findings demonstrate that a higher DI-GM score is associated with a reduced risk of female infertility, suggesting that dietary interventions targeting gut microbiota may offer a cost-effective strategy for improving reproductive health. Further longitudinal and interventional studies are warranted to confirm causality and elucidate underlying mechanisms.